Voting issues of today - Henzel, Cynthia Kennedy, 1954- (Special reports (Essential Library (Firm)), 2021)
Explores issues surrounding voting in the United States, discussing its history, contemporary issues and reforms, security and social media influence, and the role of money. Includes photographs, a list of facts, a glossary, and further resources.